“Tagapamatnubay ng Quezon” (The Counselors of Quezon): A Localized Capacity-Building Framework Based on Guidance Counselor Identity Formation - Lorzano, Zedric (Journal of Interdisciplinary Perspectives, 2026)
The focus of this research was to develop a localized capacity building framework based on the identity development of guidance counselors in Quezon Province, as revealed by their experiences and perceptions of their roles, using thematic analysis of semi-structured interviews with 22 Registered Guidance Counselors identified through purposive sampling. Thematic analysis revealed seven core themes: Theoretical Foundation, Personal Values and Beliefs, Unique Characteristics, Perceived Quezonian Guidance Counselor, Advocacies, Competencies and Skills, and Qualities and Characteristics. Together, these themes demonstrate how the professional tenets are integrated with the values of the local culture and community-oriented practice. The findings depicted "Tagapamatnubay ng Quezon" (The Counselors of Quezon) framework that structured into three categories: "Inner Core: The Being(s)", "Behavioral Manifestation: The Doing(s)", and "External Context & Impact: The Influence(s)”, serving as a localized phenomenon through which capacity-building programs may be developed, thereby providing efficient support and empowerment to future professionals and guidance counselors across the province.